Empowerment: um estudo sobre a aplicação da ferramenta em uma empresa no norte do Tocantins - Silva, Marineis Ribeiro da (Universidade Federal do Tocantins, 2020)
With the demands of the competitive market companies need to adapt to changes, seeking to develop new skills and innovate in their administrative processes. And in this context comes the concept of empowerment, a methodological approach to work which aims at empowerment, autonomy and effective participation of employees in the management of organizations. This article portrays the applicability of this approach in a service company in the city of Araguaína-TO. As methodological procedure, we used the literature and the case study. The survey results show that the company surveyed employees work with more freedom even if they tax them some limitations, such as not having the authority to make decisions alone without consulting the manager, restrictions that exist because of the surveyed company is a franchise . The organization under study focuses on cost reduction, agility and efficiency in customer service and this means it is ahead of its competitors. As one of the search results could be seen that the implementation of this tool requires commitment and responsibility of the team as a whole, will power, focus and training of people in order to obtain better results.